RANCANG BANGUN TRANSMIS MESIN PERONTOK 3600 RPM BERBASIS MOTOR BENSIN - hamdi, fahmi; Prihastuty, Endang; Tohasan, Achmad (Universitas Majalengka, 2024)
A rice threshing machine is the process of separating rice from its stems, so that reducing rice agricultural yields is very strategic in supporting rice production. Modification of the tool which previously used a slamming system, resulted in the yield of grain containing quite high levels of grain. The aim of this research is to design the transmission rotation to make the belt pulley and shaft more effective. The rice threshing machine transmission system consists of a pulley and belt with various belt sizes. The appearance of the pulley for calculations is adjusted to a pulley size of 10 inches = 25.4cm. Then the belt that connects the 10 inch/25.4cm pulley and the 9.74cm A58 belt is the belt that connects the pulley and the shaft. Based on the results of transmission performance testing with power and planning moment of 5.8164 kW and pulley planning moment of 1573.65 kg.mm from type A, the calculation of driver pulley rotation = 3 inches (d1) and motor rotation = 3600 rpm (n1) can be used rpm of the drive pulley when it is not loaded and when working, namely the rpm of the drive pulley when it is not loaded is 1080 rpm. Furthermore, the pulley rpm when working is 9.75 rpm and The design power of the shaft is 4.92 for the shear stress that occurs on the shaft of 0.838 kg/mm which is smaller than the allowable shear stress with a value of 5.16 kg/mm. so that the power and moment of planning the shaft with a diameter that can be used safely.